RF electron gun with metallic cathode - calculation and experimental study - Khodak, I.V.; Kushnir, V.A.; Mitrochenko, V.V.; Stepin, D.L.; Zhiglo, V.F. (Вопросы атомной науки и техники, 2002)
The present paper is devoted to the RF electron source design for a linear accelerator. In contrary with known RF guns with thermionic cathodes the designed electron source has high temperature metallic cathode. This permits a current pulse repetition rate to be higher significantly with saving high beam quality at the same time. Results of calculations and experimental research both on the special test set-up and in the single section electron accelerator are referred in the paper.